AMPK Phosphorylation Effect of Genistein Is Independent of GPR30. (29th May 2020) - Vásquez-Reyes, Sarai; Vargas-Castillo, Ariana; Crispin, Jose C; Rosetti, Florencia; Torres, Nimbe; Ulloa-Aguirre, Alfredo; Tovar, Armando
Abstract: Objectives: Genistein promotes fatty acid oxidation, improves glucose tolerance and increases energy expenditure. These effects are associated with AMPK phosphorylation in skeletal muscle. However, the molecular mechanism by which genistein activates the signaling pathway to activate AMPK phosphorylation is not yet known. Several target proteins have been suggested, one o them is GPR30, but it has not been studied. Thus, the aim of this study was to determine if AMPK phosphorylation by genistein is activated by GPR30. Methods: To determine if GPR30 is involved in the mechanism that promotes AMPK phosphorylation we used C2C12 GPR30 KD (knock down) myotubes obtained by transduction with a shRNA, and also GPR30 −/− primary myotubes. AMPK phosphorylation was determined via western blot in the presence of genistein after 1 hour in both cultures. Furthermore, in order to establish in vivo if the beneficial effects of genistein were associated to GPR30, C57BL/6 mice (wild type WT) and GPR30 −/− mice were fed with both control and high fat sucrose diets (HFSD) containing genistein for 2 months. During two months of treatment, weight gain, food consumption, and body composition were measured as well as a glucose tolerance test (GTT), indirect calorimetry and AMPK phosphorylation by western blot in skeletal muscle of all of groups. Results: Genistein at concentrations of 0.3, 1, 3 and 10 µ M increased AMPK phosphorylation in GPR30 KD, and GPR30 −/− primary myotubes, indicating that GPR30 is not directly involved in AMPK phosphorylation by genistein in an in vitro model. The in vivo study showed that the effect of genistein in GPR30 −/− mice on weight gain, body composition, GTT and indirect calorimetry was similar compared to wild type mice. The mice that consumed a HFSD with genistein gained less weight and less body fat, regardless of genotype (WT or GPR30 −/−). Similar effects were observed in the glucose tolerance test, oxygen exchange coefficient and oxygen consumption. Wild type and GPR30 −/− mice that consumed genistein had a better glucose tolerance than those that did not consume genistein. Conclusions: This study showed that GPR30 its not directly involved in promoting AMPK phosphorylation by genistein. In addition, genistein reduced weight gain, increased glucose tolerance and increased oxygen consumption even in the absence of GPR30. Funding Sources: INCMNSZ.